Isolation of Gemmata-Like and Isosphaera-Like Planctomycete Bacteria from Soil and Freshwater - Wang, Jenny (American Society for Microbiology, 2002)
New cultured strains of the planctomycete division (order Planctomycetales) of the domain Bacteria related to species in the genera Gemmata and Isosphaera were isolated from soil, freshwater, and a laboratory ampicillin solution. Phylogenetic analysis of the 16S rRNA gene from eight representative isolates showed that all the isolates were members of the planctomycete division. Six isolates clustered with Gemmata obscuriglobus and related strains, while two isolates clustered with Isosphaera pallida. A double-membrane-bounded nucleoid was observed in Gemmata-related isolates but not in Isosphaera-related isolates, consistent with the ultrastructures of existing species of each genus. Two isolates from this study represent the first planctomycetes successfully cultivated from soil.